Hair histology as a tool for forensic identification of some domestic animal species - Ahmed, Yasser A.; Ali, Safwat; Ghallab, Ahmed (Technische Universität Dortmund, 2018)
Animal hair examination at a criminal scene may provide valuable information in forensic investigations. However, local reference databases for animal hair identification are rare. In the present study, we provide differential histological analysis of hair of some domestic animals in Upper Egypt. For this purpose, guard hair of large ruminants (buffalo, camel and cow), small ruminants (sheep and goat), equine (horse and donkey) and canine (dog and cat) were collected and comparative analysis was performed by light microscopy. Based on the hair cuticle scale pattern, type and diameter of the medulla, and the pigmentation, characteristic differential features of each animal species were identified. The cuticle scale pattern was imbricate in all tested animals except in donkey, in which coronal scales were identified. The cuticle scale margin type, shape and the distance in between were characteristic for each animal species. The hair medulla was continuous in most of the tested animal species with the exception of sheep, in which fragmental medulla was detected. The diameter of the hair medulla and the margins differ according to the animal species. Hair shaft pigmentation were not detected in all tested animals with the exception of camel and buffalo, in which granules and streak-like pigmentation were detected. In conclusion, the present study provides a first-step towards preparation of a complete local reference database for animal hair identification that can be used in forensic investigations.
EXCLI Journal;Vol. 17 2018
Keywords: Animal hair; Veterinary forensics; Animal identification; Hair medulla; Hair scales; 610